What If I Prefer Robot Journalists? Trust and Objectivity in the AI News Ecosystem - Elena Yeste-Piquer; Jaume Suau-Martínez; Marçal Sintes-Olivella; Enric Xicoy-Comas (Journalism and Media, 2025)
The use of artificial intelligence (AI) in journalism has transformed the sector, with media generating content automatically without journalists’ involvement, and various media companies implementing AI solutions. Some research suggests AI-authored articles are perceived as equally credible as human-written content, while others raise concerns about misinformation and trust erosion Most studies focus on journalists’ views, with audience attitudes explored mainly through quantitative methods, though there is no consensus regarding the acceptability of AI use by news organizations. We explore AI’s role in journalism through audience research, conducting five focus groups to understand public perceptions. The findings highlight concerns about AI-generated content, particularly potential errors, opacity, and coldness of the content. The information is perceived as somewhat less valuable, being viewed as more automated and requiring less human effort. These concerns coexist with a certain view of AI content as more objective, unbiased, and closer to the ideal of independence from political and economic pressures. Nevertheless, citizens with more AI knowledge question the neutrality of automated content, suspecting biases from corporate interests or journalists influencing the prompts.